The acute effect of blood flow restriction or ischemia on countermovement jump performance - Bichowska-Paweska, M; Fostiak, K; Gawel, D; Trybulski, R; Alexe, D; Szura, E; Wilk, M. (Journal of Human Sport & Exercise, 2025)
The aim of this study was to evaluate the effect of blood flow restriction (BFR) or ischemia (IS) used between countermovement jumps (CMJ) on power performance changes. Two groups of participants implemented two separate experimental protocols: BFR as protocol no. 1 and IS as protocol no. 2. Protocol no. 1 involved seventeens male (n = 14) and female (n = 3). Protocol no. 2 involved twenty-three active male (n = 15) and female (n = 8). During each experimental session, following a randomized crossover design, the subjects performed 4 sets of 2 repetitions of CMJ with a 7-minute rest interval. In protocol no.1, the subjects during the rest interval used the appropriate: BFR 60%AOP or 80%AOP or control condition. In protocol no.2 subjects during the rest interval used appropriate: IS 100%AOP or control condition. The two-way repeated measures ANOVA for protocol no.1 as well for protocol no.2 did not show statistically significant condition × set interaction for average force, average power, relative peak power, relative peak force and jump height. There was also no main effect of conditions for both protocols. The results of this study indicates that neither BFR nor IS, regardless of cuff pressure, do not led to improvements in jump performance.